Academic resilience and academic performance of university students: the mediating role of teacher support - Cai, Zimo; Meng, Qian (Frontiers in Psychology, 2025)
IntroductionStudent dropout and academic failure are serious problems faced by universities around the world. The academic development of university students is the joint result of external (teacher support) and internal factors (resilience). The goal of this study is an in-depth understanding of the association between university Students’ academic resilience and academic performance.MethodsAll respondents were from a local Chinese public university. Two self-report scales with adequate reliability and validity were completed by 440 undergraduate students: the Connor-Davidson Resilience Scale (CD-RISC) and the Perceived Teacher Support Scale (PTSS).ResultsThe results of this study demonstrated that academic resilience and teacher support were positively and closely correlated with the academic performance of university students. Teacher support plays a mediating role in the nexus between academic resilience and academic performance.DiscussionThe findings of this study shed light on the improvement of university students’ academic performance and reducing the dropout rate from theoretically and practically. The study helps identify the key factors that contribute to students’ academic success and improve their well-being. The results also provide evidence for university directors to design effective programs and take initiatives to increase retention rates and improve university students’ success.